Hunter-Covey Interactions Using Pointing Bird Dogs - Theron M. Terhune II; Diana J. McGrath; Seth Wood; James A. Martin (National Quail Symposium Proceedings, 2017)
Hunting northern bobwhites (Colinus virginianus) with pointing dogs is a long-standing tradition in the Southeastern United States. Despite this rich hunting legacy, a paucity of empirical, behavioral information exists on the interaction between bobwhite coveys, pointing dogs and humans. As such, the efficiency of using pointing dogs to locate bobwhite coveys or an individual covey’s behavioral response to hunting is poorly understood. During 2013 – 2015, we conducted hunts (n = 192) by mode of foot on Tall Timbers Research Station (TTRS, 1,570 ha) in Leon County, Florida and horseback on a private property (2,023 ha) in Georgetown County, South Carolina. We captured bobwhites (n = 741) and fitted them with activity-switch enabled radio-transmitters, and we tracked coveys prior to, during and after hunts. We used 2 types of global positioning system (GPS) units to collect route data from dogs and hunters (via horseback or foot). We recorded encounter information (e.g., behavior, encounter type such as covey point or wild flush) in the field using a pre-configured application on an iPad and linked spatial data using a geographic information system (i.e., ArcGIS). On average, 52% of all radio-tagged coveys were available (within a dog’s scent radius) during a hunt of which 73% were detected by pointing bird dogs. The overall probability of observing a covey on a hunt was 38% suggesting that most coveys within a hunting course go undetected. Vegetation density did not appear to be an impediment to bobwhite mobility or an important factor in detection of coveys by bird dogs. The potential reduction or manipulation of existing habitats may help to constrain where bobwhite coveys can escape to and covertly improve hunting efficiency. Furthermore, our results imply that a relatively high bobwhite density is required for sportsman to frequently encounter bobwhite coveys during a hunt.
Keywords: colinus virginianus; northern bobwhite; bird dog; evasive behavior; hunting; radio-telemetry